MASTERY OF CONCEPTS, SCIENTIFIC ATTITUDES, AND SCIENCE PROCESS SKILLS IN INQUIRY-BASED LEARNING IN THE 5th GRADE - Suryaningsih, Tri; Ruslih, Ferry Ferdiana (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
The purpose of this study is to analyze the improvement mastery of concept, scientific attitude, and science process skill in the learning of structured and guided inquiry learning and analyzed the difference. This research was conducted in SDN Purwoyoso 02 and 03 with quasy-experiment method, experiment class 1 using structured inquiry and exeperiment class 2 using guided inquiry learning model. Data collection techniques used 20 multiple choice tests, 5 indicators of scientific attitude observation and 5 indicators observation of science process skills. Data analysis techniques use N-gain and independent samples t-test. The study showed the following results: (1) there is an increased of mastery of concepts, scientific attitudes and scientific process skills students in structured inquiry class with medium category gain. (2) there is an increase of mastery of concepts, scientific attitudes with and science process skills students in guided inquiry class with medium category gain. (3) there is a difference of mastery of concept, scientific attitude and science process skill between structured and guided inquiry class students. The result of mastery of scientific concepts, scientific attitudes, and inquiry skills of inquiry classes is higher than the structured inquiry class. The results of this study can be concluded that inquiry learning is better guided than structured inquiry.